"It's Sort of Reaffirmed to Me That I'm Not a Monster, I'm Not a Terrible Person": Sex Offenders' Movements Toward Desistance via Peer-Support Roles in Prison. (October 2018) - Perrin, Christian; Blagden, Nicholas; Winder, Belinda; Dillon, Gayle
Individuals incarcerated in prisons across the United Kingdom and abroad are able to volunteer for a variety of peer-support roles, which are characterized by prisoner-to-prisoner helping. Some research has found that such roles can represent turning points in the lives of those who have offended and encourage movements toward desistance. This proposed redemptive influence is argued to result from the prosocial behaviors that such roles appear to elicit in their holders. The present study aims to explore the mechanics of this claimed influence. While a limited amount of research has attempted this on a general offending population, no research has done so with a sample of sexual offenders. Given the intensive treatment programs involved in such contexts, and the requirements for sexual offenders to demonstrate reduced risk, the authors believe those serving time for sexual offenses represent an important sample on which to explore the potentially redemptive properties of peer-support roles. To this end, 13 peer supporters participated in semistructured interviews. Transcripts were analyzed using a phenomenologically oriented thematic analysis. Results suggest that sexual offenders who adopt peer-support roles are able to live up to desired selves by "doing good" in prison, "giving back, " and consequently resisting negative labels. These benefits have been theoretically linked with better reintegration outcomes for sexual offenders, who are publicly denigrated in the extreme and find it especially difficult to (re)integrate. Suggestions regarding the future utility of such schemes are offered.